Foreword - Birher, Nándor Máté (Verbum – Analecta Neolatina, 2023)
The priority goal of the Faculty of Humanities and Social Sciences of Pázmány Péter Catholic University is to maintain the scientific journals published by the Faculty and to promote the publication of new papers in them. To this end, an open access periodicals publishing website was created at the address ojs.ppke.hu, from which the journal Verbum – Analecta Neolatina is now also available.